At the crossroads of cancer stem cells and targeted therapy resistance. (28th January 2017) - Wang, Anbang; Qu, Le; Wang, Linhui
Abstract: Small-molecule targeted therapy (TT) has brought great hopes to patients with advanced malignancies. However, most patients suffer from tumor progression and relapse due to drug resistance. Recently, considerable efforts trying to elucidate the underlying mechanisms have focused on the contribution of cancer stem cells (CSCs) to the targeted therapy resistance (TTR). In this article, we provide an overview of the currently available literature on the rising roles of CSCs in TTR, as well as therapeutic opportunities of combining TT and anti-CSC therapy in the treatment of advanced malignancies. Graphical abstract: Highlights: CSCs are activated by TT-induced tumor environment and epigenetic modifications. CSCs mediate TTR through self-renewal, survival ability, drug efflux and dormancy. Combination treatment of TT with anti-CSC agents improve the efficacy of TT. The application of anti-CSC therapy necessitate several careful considerations.